The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/lom3.10390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lugol's iodine on long‐term preservation of marine plankton samples for molecular and stable carbon and nitrogen isotope analyses

Abstract: Carbon and nitrogen stable isotope and molecular analyses are common tools for marine ecological and biological research. However, it is difficult to fix samples for both analyses using only one preservative. A solution of potassium iodide and iodine (known as Lugol's iodine solution) is considered to be a suitable preservative; however, the effectiveness of Lugol's iodine solution for long-term preservation of samples for stable isotope analysis and molecular analysis has not yet been investigated. We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The effectiveness of 10% Lugol preservation in PCRs targeting approximately 400 bp using copepod samples has been reported (Sano et al 2020). The present study demonstrated its effectiveness in PCRs targeting over 1000 bp using various zooplankton taxa.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The effectiveness of 10% Lugol preservation in PCRs targeting approximately 400 bp using copepod samples has been reported (Sano et al 2020). The present study demonstrated its effectiveness in PCRs targeting over 1000 bp using various zooplankton taxa.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, 10% Lugol is suitable for long-term preservation of a broad range of zooplankton taxa for various molecular analyses. While there was no significant difference in the total amount of DNA extracted from S. danae between 10% Lugol preservation and freezing; the total amount of Examples of zooplankton samples preserved in 10% Lugolʼs iodine seawater (10% Lugol) for 33 months (a-i), samples preserved for 44 months (j-o), bulk zooplankton net-samples (p, q) and color of preservatives in 9 ml vials immediately after preparation (r, t) and after 18 months preservation (s, u, see Sano et al 2020). a: diphyid, b: abylid, c: copepod, d: ostracod, e: doliolid, f: polychaete, g: pteropod, h: euphausiid, i: chaetognath, j-l: Doliolum nationalis, m-o: Scolecithrix danae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both reagents have been tested as preservative in automated microbial samplings ( Boeuf et al, 2019 ; Formel et al, 2021 ; Poff et al, 2021 ), but can lead to DNA loss ( Renshaw et al, 2015 ) and are likely unsuitable in remote regions where samples cannot be frozen immediately. Hence, although automated technologies – in particular comparative sampling across different regions – offer exciting perspectives, preservation method and storage time are challenging factors for microbial diversity studies ( Sherr and Sherr, 1993 ; Rissanen et al, 2010 ; Metfies et al, 2017 ; Spens et al, 2017 ; Sano et al, 2020 ; Pratte and Kellogg, 2021 ).…”
Section: Introductionmentioning
confidence: 99%